PENGARUH INFLUENCER MARKETING TIKTOK DAN CUSTOMER EXPERIENCE TERHADAP REVISIT INTENTION PADA KIDS FRIENDLY HOTEL DI KOTA BANDUNG - Agas Maulana Ahyar; Gita Siswhara (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2026)
This study aimed to analyze the effects of TikTok influencer marketing and customer experience on revisit intention in kids-friendly hotels in Bandung City. The problem addressed was how influencer content and customer experience contributed to guests’ intention to revisit and recommend the hotel. A quantitative approach was employed using a survey method involving 200 respondents who had stayed at kids-friendly hotels and had been exposed to hotel influencer content on TikTok. Data were collected through structured questionnaires using a five-point Likert scale and were analyzed using Structural Equation Modeling with AMOS. Influencer marketing was measured through credibility, attractiveness, and content quality, while customer experience comprised functional, emotional, and relational dimensions. Revisit intention was reflected by guests’ intentions to return and to recommend the hotel to others. The results indicated that TikTok influencer marketing and customer experience had positive and significant effects on revisit intention. These findings suggested that effective influencer content management and the creation of positive customer experiences played a crucial role in enhancing guests’ intention to revisit and in fostering long-term loyalty.